Pancreatic Disease Protocols and Clinical Research - Johnson, Colin D.; Johnson, Colin D.; Imrie, Clement W.; Imrie, Clement W. (Springer London : Imprint: Springer, 2010)
Pancreatic Disease – Protocols and Clinical Research provides a clear and up-to-date review of the advancing areas in clinical pancreatology and clinical research related to the pancreas, and indentifies current research areas, suggesting most appropriate studies that need to be performed to advance knowledge in this field. Written by leading international collaborators and contributors- experts in their field- this comprehensive review directs the interested reader towards important current published source material and directs them towards the next steps in clinical research.